Wrestling on the Table: The Contemporary Wedding Meal in Latvia - Astra Spalvēna (Journal of Ethnology and Folkloristics)
The object of this paper is to examine the contemporary wedding meal in Latvia, focusing on one particular social group of well situated young couples who choose fine dining restaurants or rented venues for their wedding celebrations because they considered restaurant weddings more elaborate and modern. The desire to embrace a modern lifestyle is the way in which to obtain a new identity in a rapidly changing post-socialist world.